Partners in crime: Autoantibodies complicit in COVID‐19 pathogenesis. (5th December 2022) - Taghadosi, Mahdi; Safarzadeh, Elham; Asgarzadeh, Ali; Roghani, Seyed Askar; Shamsi, Afsaneh; Jalili, Cyrus; Assar, Shirin; Soufivand, Parviz; Pournazari, Mehran; Feizollahi, Parisa; Nicknam, Mohammad Hossein; Asghariazar, Vahid; et al.
Abstract: Autoantibodies (AABs) play a critical role in the pathogenesis of autoimmune diseases (AIDs) and serve as a diagnostic and prognostic tool in assessing these complex disorders. Viral infections have long been recognized as a principal environmental factor affecting the production of AABs and the development of autoimmunity. COVID‐19 has primarily been considered a hyperinflammatory syndrome triggered by a cytokine storm. In the following, the role of maladaptive B cell response and AABs became more apparent in COVID‐19 pathogenesis. The current review will primarily focus on the role of extrafollicular B cell response, Toll‐like receptor‐7 (TLR‐7) activation, and neutrophil extracellular traps (NETs) formation in the development of AABs following SARS‐CoV‐2 infection. In the following, this review will clarify how these AABs dysregulate immune response to SARS‐CoV‐2 by disrupting cytokine function and triggering neutrophil hyper‐reactivity. Finally, the pathologic effects of these AABs will be further described in COVID‐19 associate clinical manifestations, including venous and arterial thrombosis, a multisystem inflammatory syndrome in children (MIS‐C), acute respiratory distress syndrome (ARDS), and recently described post‐acute sequelae of COVID‐19 (PASC) or long‐COVID.